ترشيد تكاليف الإنتاج باستخدام نظام التكلفة على أساس الأنشطة - دراسة حالة مؤسسة المطاحن الكبرى للجنوب بسكرة- - محمد نجيب, دبابش; شحتاني, عبد العالي (Recherches économiques et managériales, 2020)
تهدف هذه الدراسة إلى التعرف على استخدامات نظام التكلفة على أساس الأنشطة في ترشيد تكاليف الإنتاج لمؤسسة المطاحن الكبرى للجنوب - بسكرة، والآثار الايجابية عند تطبيقه، وللإجابة عن إشكالية الدراسة واختبار فرضياتها، تم الاعتماد على المنهج الوصفي التحليلي وعلى أداة دراسة الحالة، وقد خلصت الدراسة إلى أن المؤسسة محل الدراسة تعتمد على الطريقة الكلاسيكية في تحديد تكاليفها، وهذا ما سيؤثر سلبا على وضعها التنافسي؛ ومن خلال تطبيق نظام التكلفة على أساس الأنشطة تم ترشيد تكاليف إنتاج المؤسسة مما يسمح بتحسين صورتها في نظر الزبائن وهذا من خلال توفير منتجات وفقا لاحتياجاتهم من ناحية الجودة والتكلفة. الكلمات المفتاحية: نظام التكلفة على أساس الأنشطة، الأنشطة المضيفة للقيمة، الأنشطة غير مضيفة للقيمة، التكاليف، تكاليف الإنتاج، ترشيد تكاليف الإنتاج. Résumé : Our study aims to identify the utility of using activity basedcosting method for achieving the Rationalize production costsof the GMS– Biskra- Company, and the positive effects when it applied them. To answer the study problematic and verify its hypotheses, it is based on the analytical descriptive methodology and the case study tool in the field study. The study concluded that the institution under study applies the classical method in determining their costs, which will negatively affect its competitive position. Through the application ofthe activity based costing method,The cost of production of the enterprise has been rationalized by improving the image of the institution to customers by providing products according to their needs in terms of quality, cost. Mots-clés: activity based costing system, Value-adding activities, Non-value-adding activities, Costs, Production costs, Rationalize production costs.